WOOD WASTE MATERIALS FOR EARLY CHILDHOOD EDUCATIONAL TOYS IN NEW NORMAL ERA, CASE STUDY: TOYS FOR POS PAUD FATHONAH - Rizka Rachmawati; Imtihan Hanom; Rara Siti Raudhoh (Journal of Aesthetics, Design, and Art Management, 2021)
Purpose : In this new normal era, social distancing is acknowledged as one of virus-spreading prevention acts that must be complied with. Early childhood institutions, without exception, need to provide new utilities for each student, for example, education toys. They cannot use a single toy for a group as they did before. It becomes the problem faced by educational institutions of Early Childhood, especially for Pos PAUD Fathonah. To meet the needs of educational toys, innovative materials that are suitable for a given condition are needed. This study aims to consider the wood waste utilization for educational toys. Research methods : The qualitative method is used by doing literature review about wood waste that can provide economical, safety, and durability aspects for educational toys. Findings : The result of the wood waste utilization research is expected not only to become valuable education toys, but also can reduce the environmental effect caused by wood waste itself. Implications : This research helps develop eco-friendly toys.